(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The research aims to find out the effect of feedback according to the two preferences (auditory and tactile) in learning the technical performance of the triple jump effectiveness for the students of the second stage of the Faculty of Physical Education and Sport Sciences at the University of Kirkuk, and also to compare the pre- and post-test of the three research groups that were used by the feedback according to the two preferences (auditory and tactile) in learning the technical performance of the triple jump effectiveness for the students of the second stage of the Faculty of Physical Education and Sport Sciences at the University of Kirkuk. The comparison in the post-test between my group that used feedback according to the two preferences (auditory and tactile) in learning the technical performance of the triple jump effectiveness for the students of the second stage of the Faculty of Physical Education and Sport Sciences at the University of Kirkuk, and the researcher used the experimental method to suit the nature of the research, to select the research population by the deliberate method, which are the students of the second stage at the Faculty of Physical Education and Sport Sciences, University of Kirkuk For the academic year 2018/2019, which consists of three divisions (97 students), which were selected (A, B) anddistributed into two experimental groups according to their sensory divisions, each experimental group was identified with (10) students, after completing the main experiment and conducting the post-test, and the researcher used a number of statistical methods.To reach the results, the researcher concluded that there is a positive effect of the educational programs implemented by the two experimental groups that used feedback according to sensory preferences in learning the technical performance of the triple jump effectiveness for the students of the second stage at the Faculty of Physical Education and Sport Sciences at the University of Kirkuk, as well as the existence of a clear superiority of the second experimental group that used feedback according to tactile preference) in the post-test on the two experimental groups